(untitled) (Research, Society and Development, 2022)
The aim of this qualitative study was analyzed how gender asymmetries shape and interfere in the treatment of thirty alcoholic women members of Alcoholics Anonymous (AA) in São Paulo, Brazil. Data collection was carried out through a semi-structured interview. Three categories were identified in the analysis process: “Alcoholism is a single disease, but for women it’s much worse”; “Women cannot air their intimate feeling in AA mixed meetings”; “At an AA women’s meeting I share the exact nature of my pain and it makes me stronger”. The women’s statements showed that gender asymmetries interfered decisively with the treatment of female AA members, since the women did not feel at ease discussing details of their intimate in the presence of men. It was concluding what female-only meeting is instrumental in supporting and strengthening alcoholic women in AA as a complement to the AA support group, without the pressures of gender discrimination.